Perlindungan Hukum Kerahasian Data Pribadi Konsumen Pengguna Produk Provider Telekomunikasi di Indonesia - Risa Salsabila; M. Hosen; Herlina Manik (Zaaken: Journal of Civil and Business Law, 2022)
The development of Information Technology provides extraordinary benefits for life in making it easier to carry out daily activities, on the other hand Technological Advances also provide its own concerns where every time we want to use technology we will always be bound by providing personal data as a condition for using the technology, but data The personal data holder is not properly guarded by the holder of the personal data, based on the above problems, the writer draws the formulation of the problem as follows, First, How is the legal protection of personal data in Indonesia?, Second, What is the legal protection against leakage of Consumer Personal Data? This writing uses the normative juridical method due to the ambiguity of norms due to unclear arrangements governing civil lawsuits that can be taken by victims whose personal data is misused by unscrupulous telecommunication providers, so that the results obtained are two main points, namely regarding the regulation of personal data protection which is currently regulated in Permenkominfo No. . 20 of 2016 concerning Personal Data Protection, as well as regarding the responsibility of business actors for personal data leakage, is that business actors must be ready to accept civil lawsuits submitted by consumers, and business behavior must comply with compensation in accordance with the Consumer Protection Act.   ABSTRAK Perkembangan Teknologi Informasi memberikan manfaat yang luar biasa bagi kehidupan dalam mempermudah melakukan aktifitas sehari-hari, disisi lain Kemajuan Teknologi juga memberikan kekhawatiran tersendiri yang mana setiap ingin menggunakan teknologi kita akan selalu terikat dengan memberikan data pribadi sebagai syarat untuk menggunakan teknologi tersebut, akan tetapi data pribadi tersebut tidak dijaga dengan baik oleh pemegang data pribadi, berdasarkan permasalahan diatas, maka penulis menarik rumusan masalah sebagai berikut, Pertama, Bagaimana perlindungan hukum data pribadi di Indonesia?, Kedua, Bagaimana perlindungan hukum terhadap kebocoran Data Pribadi Konsumen? Penulisan ini menggunakan metode yuridis normatif dikarenakan terjadinya kekaburan norma dikarenakan ketidakjelasan pengaturan yang mengatur gugatan perdata yang dapat ditempuh oleh korban yang data pribadinya disalahgunakan oleh oknum provider telekomunikasi, sehingga diperoleh hasil terdapat dua point utama yaitu mengenai pengaturan perlindungan data pribadi saat ini diatur dalam Permenkominfo No. 20 Tahun 2016 tenteng Perlindungan data Pribadi, serta mengenai tanggung jawab pelaku usaha terhadap kebocoran data pribadi adalah pelaku usaha harus siap menerima gugatan perdata yang diajukan konsumen, dan perlaku usaha harus taat dengan melakukan ganti rugi sesuai dengan undang-undang Perlindungan Konsumen.